Perilaku Berolahraga dalam Menghadapi Keluhan Menopause - Yusnita, Laila Erni; Cahyo, Kusyogo (Jurnal Promosi Kesehatan Indonesia, 2010)
About 75% women who have menopause feel it trouble, but 25% not. This study aims to analyze factors influencing exercise behavior to face the menopause syndrome at members of PORPI Tambak Mas Semarang City. It was a cross sectional explanatory study employed quantitative and qualitative approach. Respondents were all of the population, women 40 – 55 years old, and 49 samples. One branch manager and two subsection manager were in –depth interviewed in qualitative part. Most of respondents were 50 – 55 years old, not working (55, 1%), high educated (81, 6%) and good in exercise behavior (73,5%). Women’s knowledge on menopause and all of syndrome mostly (57, 1%) categorized in low level, perceived susceptibility, seriousness of the menopause syndrome mostly good (55,1%) and 61,2%). Perceived barriers of the exercise and cues to action categorized in high level (69,4% and 53,1%). Perceived benefits of the exercise were significantly correlated to exercise behavior. Age, education attainment, knowledge, perceived susceptibility and seriousness of the menopause syndrome were not correlated. Multivariate analysis showed that there were no independent variables dominated to exercise behavior.